2016
DOI: 10.1038/srep24793
|View full text |Cite
|
Sign up to set email alerts
|

Thioflavin T as an efficient fluorescence sensor for selective recognition of RNA G-quadruplexes

Abstract: RNA G-quadruplexes (G4s) play important roles in translational regulation, mRNA processing events and gene expression. Therefore, a fluorescent probe that is capable of efficiently recognizing RNA G-quadruplex structures among other RNA forms is highly desirable. In this study, a water-soluble fluorogenic dye (i.e., Thioflavin T (ThT)) was employed to recognize RNA G-quadruplex structures using UV-Vis absorption spectra, fluorescence spectra and emission lifetime experiments. By stacking on the G-tetrad, the T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
110
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 139 publications
(119 citation statements)
references
References 40 publications
(37 reference statements)
2
110
0
1
Order By: Relevance
“…First, there are two negative Cotton effects located at 301 and 311 nm, which show red-shift relative to Fmoc-Glu/A. [11] It is reported that the fluorescence of ThTi ncreases remarkably when it is bound to amyloid fibers or other hydrophobic patches because its freely rotating aromatic rings become fixed. Although Fmoc-Glu/T showed CD signals,i td id not exhibit obvious helical nanostructures.T his indicates that Aa nd Gi nduced more effective expression of helicity in the assemblies than Tand C. Thef luorescence spectra of Fmoc-Glu with four nucleobases are shown in Figure 2D.I nc omparison with plain Fmoc-Glu, Aa nd Gc ause ar ed-shift in the fluorescence emission, while Ta nd Ca lmost maintain the Fmoc-Glu emission, indicating that in the Fmoc-Glu/A (G) system, p-p stacking is stronger than that of the T( C) system.…”
Section: Angewandte Chemiementioning
confidence: 99%
See 1 more Smart Citation
“…First, there are two negative Cotton effects located at 301 and 311 nm, which show red-shift relative to Fmoc-Glu/A. [11] It is reported that the fluorescence of ThTi ncreases remarkably when it is bound to amyloid fibers or other hydrophobic patches because its freely rotating aromatic rings become fixed. Although Fmoc-Glu/T showed CD signals,i td id not exhibit obvious helical nanostructures.T his indicates that Aa nd Gi nduced more effective expression of helicity in the assemblies than Tand C. Thef luorescence spectra of Fmoc-Glu with four nucleobases are shown in Figure 2D.I nc omparison with plain Fmoc-Glu, Aa nd Gc ause ar ed-shift in the fluorescence emission, while Ta nd Ca lmost maintain the Fmoc-Glu emission, indicating that in the Fmoc-Glu/A (G) system, p-p stacking is stronger than that of the T( C) system.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…Thioflavin T(ThT), as the most popular fluorescent probe,is used for the detection of amyloid fibers and also to study gel formation, due to its environment-dependent emission behavior. [11] It is reported that the fluorescence of ThTi ncreases remarkably when it is bound to amyloid fibers or other hydrophobic patches because its freely rotating aromatic rings become fixed. [12] In this context, ThTw as selected as an indicator to investigate whether the chiral sense of the helix in Fmoc-Glu/A (G) transferred to the achiral moiety.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…Such chemical scaffolds are interesting as potentialt herapeutics, for example, the G4-binding compound quarfloxin (CX-3543) reached phase II clinical trials, [12] and as chemicalr esearch tools to furthers tudy the biological functions of G4 structures. [16] We first confirmed that ThT emits af luorescent signal when bound to differentG4structures and then demonstrated that the fluorescent signal was significantly reduced upon displacement of ThT by the G4 ligand PhenDC3. [14] Herein, we have developedacost-effective HTS to find selective G4-binding compounds without utilizing labeled oligonucleotides.…”
Section: Introductionmentioning
confidence: 62%
“…The HTS process wasb ased on the fluorescent lightup probe Thioflavin T( ThT), [15] which shows selectivity for G4 DNA and G4 RNA over single-or double-stranded DNA (dsDNA). [16] We first confirmed that ThT emits af luorescent signal when bound to differentG4structures and then demonstrated that the fluorescent signal was significantly reduced upon displacement of ThT by the G4 ligand PhenDC3. Therefore, this assay [17] was developed to be used in aH TS format.…”
Section: Introductionmentioning
confidence: 99%
“…Recombinant purified DDX21 showed marginally higher affinity for TV2 vs TV2m (100nm vs 300nm) TV2 and TV2m were assayed for rG4 formation by ThT, a fluorescent probe for RNA rG4 formation 35,36 . When ThT is bound to rG4 it exhibits enhanced fluorescence.…”
Section: In Vitro Evidence Of Rg4 Formationmentioning
confidence: 99%